Indian Ocean tsunami deposits along the West Coast of the Malay-Thai Peninsula: foraminiferal and grain size analysis - Hawkes, Andrea D.; Bird, Micheal; Cowie, Susan; Horton, Benjamin; Nott, Jonathan; Robinson, Ruth; Aik, Lee Wan (Anuário do Instituto de Geociências, 2006)
Abstract